A New Generation of Cell Therapies Employing Regulatory T Cells (Treg) to Induce Immune Tolerance in Pediatric Transplantation - Bernaldo-de-Quirós, Esther; Pion, Marjorie; Martínez-Bonet, Marta; Correa-Rocha, Rafael (Frontiers in Pediatrics, 2022)
Kidney transplantation is the most common solid organ transplant and the preferred treatment for pediatric patients with end-stage renal disease, but it is still not a definitive solution due to immune graft rejection. Regulatory T cells (Treg) and their control over effector T cells is a crucial and intrinsic tolerance mechanism in limiting excessive immune responses. In the case of transplants, Treg are important for the survival of the transplanted organ, and their dysregulation could increase the risk of rejection in transplanted children. Chronic immunosuppression to prevent rejection, for which Treg are especially sensitive, have a detrimental effect on Treg counts, decreasing the Treg/T-effector balance. Cell therapy with Treg cells is a promising approach to restore this imbalance, promoting tolerance and thus increasing graft survival. However, the strategies used to date that employ peripheral blood as a Treg source have shown limited efficacy. Moreover, it is not possible to use this approach in pediatric patients due to the limited volume of blood that can be extracted from children. Here, we outline our innovative strategy that employs the thymus removed during pediatric cardiac surgeries as a source of therapeutic Treg that could make this therapy accessible to transplanted children. The advantageous properties and the massive amount of Treg cells obtained from pediatric thymic tissue (thyTreg) opens a new possibility for Treg therapies to prevent rejection in pediatric kidney transplants. We are recruiting patients in a clinical trial to prevent rejection in heart-transplanted children through the infusion of autologous thyTreg cells (NCT04924491). If its efficacy is confirmed, thyTreg therapy may establish a new paradigm in preventing organ rejection in pediatric transplants, and their allogeneic use would extend its application to other solid organ transplantation.